Information sharing in community associations: Asian immigrants' experiences. Issue 1 (2015) - Khoir, Safirotu; Du, Jia Tina; Koronios, Andy
ABSTRACT: Dealing with information in a new land is considered challenging for immigrants. Their adaptation process, including how to seek and share information, usually requires supports from several sources, including various social and community associations. This paper discusses immigrants' information sharing practices within community groups during their settlement processes. Data for analysis includes 197 questionnaires, 35 interviews, and 258 photos. The preliminary results show that Asian immigrants are involved in community associations and online links with both general and particular groupings. The main sharing activities relate to daily activities, culture and religion and knowledge/experience. The findings will provide insights of how sharing activities within community associations support immigrants' settlement.